Faktor-Faktor yang Menyebabkan Melemahnya Nilai Tukar Mata Uang Rupiah Terhadap Nilai Tukar Mata Uang Asing - Julaikha Nur Fadhilah (Universitas Islam Negeri Sumatera Utara, 2022)
This journal was created to analyze the results of research on several factors that made the rupiah exchange rate weaken. Several factors regarding this, such as the inflation rate, money supply, interest rates, and Indonesia's international balance of payments affect the movement of the exchange rate against the US dollar. The method used is the documentary method, which conducts research from reports or other journal data. for the analysis technique using the Error Correction Model (ECM) technique. From the research results, it can be proven that the inflation rate, interest rate and money supply can affect the exchange rate of the rupiah against the US dollar. This is explained about some of the results of the data that the researcher uses, as well as the calculation of the comparison of several factors between the exchange rate of the rupiah and the US dollar. In the short and long term, inflation rates, interest rates, exports and imports also affect the weakening of the exchange rate in Indonesia. So, if you look at some of the existing problems, Bank Indonesia should pay more attention to interest rates and the running of domestic inflation. In addition, the government should improve the quality of domestic products, in order to be able to compete with foreign countries whose products are of good quality.